Pragmatic Features of the Word Order in Speech - Sobirov Anvar Kuvandikovich (International Journal on Integrated Education, 2022)
Language is the main tool that ensures the emergence of human thoughts. Therefore, the concept of speech activity is realized in close connection with pragmatics, which denotes the Greek meanings "work", "activity". Although the structure of words in a sentence in a certain order is considered the law inherent in all manifestations of speech, in artistic speech, along with all units, the word order provides for a certain communicative goal, the formation of expressive colloquial expressions. In the process of mutual communication, the activation and arising affectivity of a particular piece of speech in connection with the communicative goal of the speaker or writer intersects within the framework of pragmatics as an important semantic and communicative category, in which the speaking subject rises to the fore with his goal.